Practical consequences of model misfit when using rating scales to assess the severity of attention problems in children - Crișan, Daniela R. (Int J Methods Psychiatr Res, 2019)
OBJECTIVES: In this study, we examined the consequences of ignoring violations of assumptions underlying the use of sum scores in assessing attention problems (AP) and if psychometrically more refined models improve predictions of relevant outcomes in adulthood. METHODS: Tracking Adolescents' Individual Lives data were used. AP symptom properties were examined using the AP scale of the Child Behavior Checklist at age 11. Consequences of model violations were evaluated in relation to psychopathology, educational attainment, financial status, and ability to form relationships in adulthood. RESULTS: Results showed that symptoms differed with respect to information and difficulty. Moreover, evidence of multidimensionality was found, with two groups of items measuring sluggish cognitive tempo and attention deficit hyperactivity disorder symptoms. Item response theory analyses indicated that a bifactor model fitted these data better than other competing models. In terms of accuracy of predicting functional outcomes, sum scores were robust against violations of assumptions in some situations. Nevertheless, AP scores derived from the bifactor model showed some superiority over sum scores. CONCLUSION: These findings show that more accurate predictions of later‐life difficulties can be made if one uses a more suitable psychometric model to assess AP severity in children. This has important implications for research and clinical practice.